2012
DOI: 10.1111/j.1467-6494.2011.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive Intelligence Illusions: On the Relation Between Intellectual Self‐Enhancement and Psychological Adjustment

Abstract: The relation between self-enhancement and psychological adjustment has been debated for over 2 decades. This controversy is partly due to the variety of approaches implicated in the assessment of mainly self-enhancement but also psychological adjustment. We adopted a face-valid approach by statistically removing actual intellectual ability variance from self-rated intellectual ability variance. Study 1 (N = 2,048), a concurrent Internet investigation, provided initial insight into the relation between intellec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 86 publications
7
75
0
Order By: Relevance
“…Indeed self-enhancement and temptation entail distinct psychological correlates. Self-enhancement is linked to better physical health (Segerstrom & Roach, 2008;Taylor, Kemeny, Reed, Bower, & Gruenewald, 2000;Taylor, Lerner, Sherman, Sage, & CHRISTIAN SELF-ENHANCEMENT 41 McDowell, 2003a) and better psychological health (Dufner et al, 2012;Marshall & Brown, 2008;Sedikides, Rudich, Gregg, Kumashiro, & Rusbult, 2004), whereas giving in to temptations is linked to worse physical and psychological health (materialism- Kasser & Ryan, 1993;drug use-Adams, Blanken, Ferguson, & Kopstein, 1990;drug use-Ybarra & Mitchell, 2005).…”
Section: Christian Self-enhancement 40mentioning
confidence: 99%
“…Indeed self-enhancement and temptation entail distinct psychological correlates. Self-enhancement is linked to better physical health (Segerstrom & Roach, 2008;Taylor, Kemeny, Reed, Bower, & Gruenewald, 2000;Taylor, Lerner, Sherman, Sage, & CHRISTIAN SELF-ENHANCEMENT 41 McDowell, 2003a) and better psychological health (Dufner et al, 2012;Marshall & Brown, 2008;Sedikides, Rudich, Gregg, Kumashiro, & Rusbult, 2004), whereas giving in to temptations is linked to worse physical and psychological health (materialism- Kasser & Ryan, 1993;drug use-Adams, Blanken, Ferguson, & Kopstein, 1990;drug use-Ybarra & Mitchell, 2005).…”
Section: Christian Self-enhancement 40mentioning
confidence: 99%
“…In schoolchildren, overconfidence in academic achievement (compared to grades) was associated with higher self-esteem and wellbeing across Israeli and Singaporean samples (Kurman & Eshel, 1998;Kurman & Sriram, 1997), though not with teacher-rated adjustment. Overconfidence in vocabulary skills has been associated with higher self-esteem, life satisfaction, positive affect, and lower levels of depression (Dufner et al, 2012). Participants who score higher on the OCQ have higher levels of self-esteem (Paulhus et al, 2003).…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…The strongest effects were found when nominating someone they would ask for help or would like to work with, though there were also some positive effects when nominating individuals as friends. In a different study, (Dufner et al, 2012) found that individuals who were overconfident in their vocabulary were rated as more likable, though not more agreeable, by their peers. Thus, cross-sectional studies seem to indicate that overconfidence conveys increased competence, at least in the relevant domain, and that it also has status-enhancing effects.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 2 more Smart Citations